On the concept of intensive development of education and science in conditions of transition to a knowledge society - Юлдашев, Сергій Олексійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article considers the elements of the concept of intensive development of education and science in conditions of transition to the knowledge society. In particular, we propose the concept of innovative education as an educational system, where the educational information contains the maximum possible amount of knowledge about innovations, innovations, and ideally consists only of them. It is about innovative educational programs containing (should contain) information about the most effective ideas, inventions, discoveries. To ensure the constant innovation of scientific programs, mechanisms are needed to systematically replenish them with new scientific information, implement the output of scientific research results («exit» of science) in education, educational standards: educational and qualification characteristics, educational and qualification programs, educational and professional programs OPP) and curricula - as an «input» to education.